2009
DOI: 10.1055/s-0029-1211246
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulatory Effect of Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) on LH Release from Rat Pituitary Cells in Vitro Does not Involve Calcium Mobilization

Abstract: The hypothalamic peptide "pituitary adenylate cyclase activating polypeptide (PACAP)" stimulates cAMP production in cultured rat pituitary cells and enhances LH release. It has been suggested that the stimulation of LH release by PACAP comprises two distinct mechanisms: a direct stimulatory action on LH secretion and a potentiation of the response of the gonadotrophes to LHRH. Thus the possibility exists that PACAP may enhance LH secretion not only by increased cAMP production but also by increasing cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Similarly, a calcium-independent metabolic activation was found previously in other systems, e.g. the stimulatory effect of pituitary adenylate cyclase-activating peptide on luteinizing hormone release from rat pituitary [53]. …”
Section: Discussionsupporting
confidence: 68%
“…Similarly, a calcium-independent metabolic activation was found previously in other systems, e.g. the stimulatory effect of pituitary adenylate cyclase-activating peptide on luteinizing hormone release from rat pituitary [53]. …”
Section: Discussionsupporting
confidence: 68%
“…Cytofluorimetric studies, conducted on dispersed rat pituitary cells, have shown that PACAP, acting through three different mechanisms, induces calcium elevation in all categories of endocrine cells Gracia-Navarro et al, 1992;Rawlings et al, 1993Rawlings et al, , 1994Rawlings and Hezareh, 1996;Alarcón and García-Sancho, 2000). Consistent with this observation, PACAP stimulates the release of GH, adrenocorticotropin, LH, follicle-stimulating hormone (FSH), PRL (Goth et al, 1992;Hart et al, 1992;Coleman and Bancroft, 1993;Koch and Lutz-Bucher, 1993;Perrin et al, 1993;Arbogast and Voogt, 1994;Hashizume et al, 1994;Velkeniers et al, 1994;Coleman et al, 1996;Martínez-Fuentes et al, 1998c;Ortmann et al, 1999) and somatolactin (Azuma et al, 2009). The effects of PACAP on the different pituitary cell types are summarized in Table 9.…”
Section: B Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 70%
“…In particular, VIP and to a lesser extent PHI and secretin stimulate PRL secretion (Vijayan et al, 1979;Enjalbert et al, 1980;Kimura et al, 1987;Muratori et al, 1994;Judd, 1995;Youngren et al, 1998). In fact, PACAP is more potent than other members of the family in stimulating PRL secretion because intrave- Miyata et al, 1989;Culler and Paschall, 1991;Canny et al, 1992;Gracia-Navarro et al, 1992;Leonhardt et al, 1992;Perrin et al, 1993;Rawlings et al, 1993;Hashizume et al, 1994;Garrel et al, 2002 Somatotrope cells 1 cAMP, 1 ͓Ca 2ϩ ͔ i 1/3 GH release Miyata et al, 1989;Canny et al, 1992;Goth et al, 1992;Gracia-Navarro et al, 1992;Hart et al, 1992;Jarry et al, 1992;Leonhardt et al, 1992;Nagy et al, 1993;Rawlings et al, 1993;Wei et al, 1993;Yada et al, 1993;Hashizume et al, 1994;Velkeniers et al, 1994;Rousseau et al, 1999;Wong et al, 2005; Miyata et al, 1989;Gracia-Navarro et al, 1992;Hart et al, 1992;Jarry et al, 1992;Leonhardt et al, 1992;Nagy et al, 1993;Arbogast and Voogt, 1994;Hashizume et ...…”
Section: B Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…Evidence that ADCYAP1 can induce gonadotropin release by a direct action at the pituitary was obtained mainly through in vitro studies using anterior pituitary cells or gonadotroph cell lines. A physiological concentration of ADCYAP1 increases LH and FSH as well as free common alpha-glycoprotein subunit (CGA) release in normal gonadotrophs [8,[10][11][12]. The stimulatory effects of ADCYAP1 on gonadotropin production also are evident in single gonadotroph cell models, such as aT3-1 cells or LbT2 cells [13,14].…”
Section: Introductionmentioning
confidence: 99%